2024
DOI: 10.1002/iid3.1257
|View full text |Cite
|
Sign up to set email alerts
|

Maternal awareness, acceptability and willingness towards respiratory syncytial virus (RSV) vaccination during pregnancy in Ireland

Siobhan McCormack,
Claire Thompson,
Miriam Nolan
et al.

Abstract: BackgroundRespiratory syncytial virus (RSV) is the world's leading cause of viral acute lower respiratory infections (ALRI) in infants. WHO has identified maternal RSV vaccination a priority and candidate vaccines are in development; however, vaccine hesitancy remains an impediment to successful implementation of maternal immunization. This study, the largest antenatal survey conducted to‐date, aimed to examine maternal RSV awareness, likely acceptance of RSV vaccination in pregnancy, and attitudes to maternal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…Therefore, the high number of pregnant women that opts for pertussis vaccination in our cohort might also explain the high number of parents favouring maternal vaccination over neonatal immunization. A high proportion of our study population (91.2%) showed willingness to maternal vaccination which was much higher compared to previous reports that ranged from 48.5 to 77% 20 21 23 24 . Reasons for this could be the overall high vaccination willingness and high familiarity with RSV in this study, which has been suggested as a strong predictor for vaccine uptake before 23 .…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Therefore, the high number of pregnant women that opts for pertussis vaccination in our cohort might also explain the high number of parents favouring maternal vaccination over neonatal immunization. A high proportion of our study population (91.2%) showed willingness to maternal vaccination which was much higher compared to previous reports that ranged from 48.5 to 77% 20 21 23 24 . Reasons for this could be the overall high vaccination willingness and high familiarity with RSV in this study, which has been suggested as a strong predictor for vaccine uptake before 23 .…”
Section: Discussioncontrasting
confidence: 78%
“…To date, most studies exploring the acceptance of RSV prophylactic strategies have primarily focused on maternal vaccination alone 20 21 23 24 , despite the fact that most countries are willing to implement neonatal immunization. A small number of recently published studies did evaluate the acceptability of both strategies among parents of children < 2 years old, pregnant women and health care professionals 22 25 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation